REACH Beyond Borders : Europeanization Towards Global Regulation - Filipec, Ondřej (Springer International Publishing : Imprint: Springer, 2017)
This book discusses how much other countries reflect the EU chemical regulation REACH (Registration, Evaluation, Authorization, Restriction of Chemicals), in the context of Europeanization theory. The main hypothesis verified in this book is that more trade with the EU means more Europeanization (as the non-EU companies exporting to the EU have an obligation to comply with EU rules according to the "No data, No Market" REACH provision). This book further points out that non-EU companies voluntarily adopt EU standards while this change has yet to be reflected on the policy level in non-EU countries, mainly for economic reasons. Exploring changes in national chemical regulatory policies among top chemical producers around the World brings new ideas into the process of Europeanization behind EU borders and provides useful material for academia, regulatory experts and export oriented chemical industry.
Keywords: Chemistry.; Chemical engineering.; International environmental law.; Industrial organization.; European Economic Community literature.; Environmental policy.; elektronické knihy; electronic books